Depression and Anxiety in the Qur'anic Perspective : Analysis of the Interpretation of the Verses of Huzn and Khauf According to Maudhu'i Al-Farmawi's Tafsir Theory - Firly Hidayanti; Agus Hidayat (Journal of Ulumul Qur'an and Tafsir Studies, 2023)
increasingly common in modern society. From the perspective of the Koran, there are verses that discuss feelings of sadness and fear. Tafsir of the Verses Huzn and Khauf according to Maudhu'i Al-Farmawi's Tafsir Theory provides an insight into how the Koran views these feelings. This research aims to analyze the Koran's views on depression and anxiety through the interpretation of the verses Huzn and Khauf according to Maudhu'i Al-Farmawi's theory of interpretation. The research method used is qualitative analysis of the interpretation of the verses Huzn and Khauf according to Maudhu'i Al-Farmawi's theory of interpretation. The research results show that the Koran views feelings of sadness and fear as part of life's trials that humans must face. The Koran also provides solutions to overcome these feelings, such as by praying and increasing worship. This research contributes to expanding understanding of the Koran's views on depression and anxiety.